Direct Method on Students’ Pronunciation - Hutahean, Saimarito; Hamka, Hamka; Minda, Sri (English Education : English Journal for Teaching and Learning, 2024)
This research investigates the impact of Direct Method on students' pronunciation. The study uses a quantitative, quasi-experimental approach with pre-test, treatment, and post-test data. The sample consisted of 49 grade XII students. Data was collected through oral tests with 25-word items. The result can be seen from the mean score in the pre-test to the post which have enhancement. It can be proved that Direct Method can affect to students’ pronunciation at grade XII in Islamic Senior High School of Mardhatillah.